2021
DOI: 10.3389/fpsyg.2021.671663
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Leadership and Career Sustainability: Mediating Roles of Supervisor Developmental Feedback and Thriving at Work

Abstract: Career sustainability is a well-researched issue in academics and other sectors. Technology advancements and COVID-19 have jeopardized career sustainability. Numerous studies have explored the influence of individual characteristics on career sustainability, but few have focused on leadership. In addition, cultural factors must be considered because leadership is rooted in culture. In particular, inclusive leadership reflects traditional Chinese culture. Therefore, based on self-determination social exchange t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 103 publications
2
25
0
Order By: Relevance
“…Socially responsible organizations treat their leaders as valued resources and attempt to convert them into happy leaders who willfully put forth the organizational objectives, including the sustainability objectives [ 47 , 48 ]. A positive link between CSR and leadership style has also been reported in previous works [ 49 , 50 ]. In this regard, transformational leaders are at the heart of a socially responsible organization to implement different social initiatives and to clarify the followers about the seriousness of an organization for CSR-related objectives [ 51 ].…”
Section: Methodssupporting
confidence: 81%
“…Socially responsible organizations treat their leaders as valued resources and attempt to convert them into happy leaders who willfully put forth the organizational objectives, including the sustainability objectives [ 47 , 48 ]. A positive link between CSR and leadership style has also been reported in previous works [ 49 , 50 ]. In this regard, transformational leaders are at the heart of a socially responsible organization to implement different social initiatives and to clarify the followers about the seriousness of an organization for CSR-related objectives [ 51 ].…”
Section: Methodssupporting
confidence: 81%
“…Thus, engaging leadership effective in achieving corporate objectives is the hallmark of a socially responsible organization [45]. Different researchers have argued about the direct association between CSR and the inclusive behavior of a leader [46,47]. To conclude, CSR as a business imperative can generate real consequences for various stakeholders by implementing ethical values and sustainable work practices in an organization.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…As Rupprecht et al (2019) found, mindfulness training caused changes in leaders’ cognitive nervous system, their behaviors were further affected, and their self-leadership was improved. On that account, leaders’ inclusive leadership ( Fang et al, 2019 , 2021 ) was also promoted, and their employees’ failures would be understood and tolerated. In the same way, mindfulness self-leadership enables learners to focus on and be sensitive about the learning environment and make inclusive decisions considerately and comprehensively about their learning engagement and even learning failure.…”
Section: Discussionmentioning
confidence: 99%